Surfactant effect on the kinetics of mixed hydrogen/propane hydrate formation for hydrogen storage as clathrates. (14th April 2015) - Veluswamy, Hari Prakash; Chen, Jian Yu; Linga, Praveen
Abstract: Effect of sodium dodecyl sulfate (SDS) surfactant on the kinetics of mixed hydrogen/propane hydrates was studied extensively in a stirred tank reactor. SDS concentration was varied in the range of 5–1000 ppm and its effect on the kinetics of the mixed hydrogen hydrate formation was observed. Anionic SDS surfactant drastically improved the rate of mixed hydrate formation due to which the hydrate formation time reduced significantly. The time required for 90% completion of the hydrate formation reduced from 334.2 (±27.7) min (water without any surfactant) to just 25.5 (±1.8) min in presence of SDS surfactant at concentrations greater than or equal to 100 ppm. The presence of SDS resulted in a distinct two step hydrate growth mechanism. Hydrate growth behavior similar to control (water) experiments was observed from nucleation till certain time (deflection time) beyond which the surfactant exhibited its property and increased the rate of hydrate formation resulting in faster completion of mixed hydrogen hydrate formation. Graphical abstract: Highlights: Anionic SDS surfactant effect on the formation of H2 /Propane mixed hydrates in STR. Observation of a distinct two step hydrate growth mechanism using SDS surfactant. Significant improvement in the rate of mixed hydrate formation using surfactant. t 90 Reduced from 5.6 h to 0.4 h using SDS surfactant (at concentration ≥100 ppm).